2008
DOI: 10.1074/jbc.m801342200
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Transcription Factor B2 Is Essential for Metabolic Function in Drosophila melanogaster Development

Abstract: Characterization of the basal transcription machinery of mitochondrial DNA (mtDNA) is critical to understand mitochondrial pathophysiology. In mammalian in vitro systems, mtDNA transcription requires mtRNA polymerase, transcription factor A (TFAM), and either transcription factor B1 (TFB1M) or B2 (TFB2M). We have silenced the expression of TFB2M by RNA interference in Drosophila melanogaster. RNA interference knockdown of TF2BM causes lethality by arrest of larval development. Molecular analysis demonstrates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 47 publications
4
25
0
Order By: Relevance
“…This is supported by the phenotype observed in several other Drosophila mitochondrial gene mutants. For example, knockdown of mtTFB2, which encodes the mitochondrial transcription factor B2, or mutations in mitochondrial single-stranded DNA-binding protein, both involved in mtDNA replication, also cause a developmental delay and a developmental arrest in the third larval instar (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by the phenotype observed in several other Drosophila mitochondrial gene mutants. For example, knockdown of mtTFB2, which encodes the mitochondrial transcription factor B2, or mutations in mitochondrial single-stranded DNA-binding protein, both involved in mtDNA replication, also cause a developmental delay and a developmental arrest in the third larval instar (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…The diminished PRC mRNA expression is associated with a reduction in the mRNAs encoding the mitochondrial transcription factors (TFAM, TFB1M, and TFB2M). The biggest decrease is in TFB2M, whose expression has recently been correlated with the transcription and replication of mtDNA in both human (34) and Drosophila (35) cells. Here, we observe the down-regulation of three mitochondrial transcripts ( Fig.…”
Section: Isolation Of Lentiviral Transductants Of U2os Cells Exhibitimentioning
confidence: 99%
“…h-mtTFB2 has been reported to have substantially higher, transcription-stimulating activity in vitro than h-mtTFB1 (21). However, studies in vivo only support a role for mtTFB2 in transcription, with mtTFB1 contributing to translation (23)(24)(25)(26). Recently, it was shown that the amino-terminal region of h-mtTFB2 interacts with the TSS, stabilizing the melted promoter and the initiating nucleotide (27).…”
mentioning
confidence: 99%